Linguistic Properties of Metamodernist Concepts in Anglophone Art Discourse (Case of Modern Scottish Prose) - N. F. Shcherbak; A. I. Gerus (Дискурс, 2022)
Introduction. The article attempts to identify the main trends in the development of modern works of Scottish prose. The main aim is to consistently identify linguistic means and mechanisms for implementing the characteristic features of metamodernism, comprehending changes in the authors’ views on the text as well as their choice of tools for interaction with recipients.Methodology and sources. The starting point for the methodology is the description by Robin van den Acker and Timotheus Vermeulen of the key vectors of modern literature development under the umbbrella of such a phenomenon as metamodernism, which reveals both its inevitable kinship with postmodernism and its own philosophical and aesthetic aspirations.Results and discussion. When compared with writing samples exemplifying innovations and traditions of other times and related cultures, the set of modern Scottish prose texts under analysis reveals trends towards the regular use of such techniques as intertextuality, rhizome as a structural model, rejection of traditional methods for constructing time and space, rethinking of the motives and plots from the cultural archives. The introduction of innovative storytelling styles provides opportunities for addressing acute social issues and previously tabooed topics.Conclusion. It is the texts of Scottish literature that seem to facilitate a vivid illustration of modern metamodernist, and in particular neorealist tendencies: the desire to turn to the past in order to deconstruct it, experiment with genre, create opportunities for free reading. However, the culture and traditions of Scotland invariably manifest themselves in the literary practices implemented by the prose writers. Thus, in Scottish prose, the general literary trends and the cultural specifics of the country are intertwined in a unique combination.